2016
DOI: 10.2807/1560-7917.es.2016.21.12.30171
|View full text |Cite
|
Sign up to set email alerts
|

The effect of migration within the European Union/European Economic Area on the distribution of tuberculosis, 2007 to 2013

Abstract: Immigration from tuberculosis (TB) high-incidence countries is known to contribute notably to the TB burden in low-incidence countries. However, the effect of migration enabled by the free movement of persons within the European Union (EU)/European Economic Area (EEA) on TB notification has not been analysed. We analysed TB surveillance data from 29 EU/EEA countries submitted for the years 2007-2013 to The European Surveillance System. We used place of birth and nationality as proxy indicators for native, othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 21 publications
1
8
2
Order By: Relevance
“…This is not consistent with data reported at EU level: the countries reporting most TB cases originating from other EU/EEA were Germany and Italy [26]. …”
Section: Discussioncontrasting
confidence: 97%
“…This is not consistent with data reported at EU level: the countries reporting most TB cases originating from other EU/EEA were Germany and Italy [26]. …”
Section: Discussioncontrasting
confidence: 97%
“…This notification rate is lower than that of migrants to other European countries such as the United Kingdom, as reported previously in the literature [5]. It could be thus hypothesised that in comparison with Italy, EU/EEA countries with higher percentages of migrants from countries with a higher TB burden might have persistently higher TB notification rates among foreign born TB cases [6]. …”
supporting
confidence: 49%
“…24,32 The most systematic evidence of the TB burden, including that for TB and MDR-TB disease among migrants, comes from low TB incidence countries in Europe and North America, where foreign-born persons sometimes account for more than half of the TB incidence; migrants also often have higher rates of MDR-TB. 38,[49][50][51][52][53][54][55][56][57] Studies have also reported a high prevalence of tuberculous infection or active TB disease in migrant children, as well as among immigrants and migrant workers in low TB incidence countries in other regions, such as the Middle East. 58,59 In Lebanon, the increasing TB burden in recent years has been associated with increased numbers of migrants, including from high TB burden countries, and large numbers of refugees displaced by the conflict in neighbouring Syria; some studies have shown that despite their origins in a low TB incidence setting, Syrian refugees in Jordan have higher rates of disease.…”
Section: Migration Pathways Social Determinants Of Health and Tubercmentioning
confidence: 99%